The influencing factors of citizen of Bandung preferences towards dental quack on constructing custom-made orthodontic appliances - Zakyah, Akhyar Dyni; Rosabella, Shekarwangi; Hafizoh, Nuzulul; Laviana, Avi; Setiawan, Asty Samiaty (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Introduction: Braces often used in the treatment of malocclusion. However, in recent years malocclusion no longer becomes the reason for orthodontic treatment. Many people use it merely for a lifestyle purpose, and most of them got it from the dental quack. This study was aimed to understand the influencing factors of the citizen of Bandung preferences towards dental quack on constructing custom-made orthodontic appliances. Methods: This study was a cross-sectional study with purposive sampling technique consisted of 30 samples. The inclusion criteria were subject wearing dental quack custom-made orthodontic appliance; citizen of Bandung; and willing to participate in the study. Exclusion criteria were subject refused to participate in the study. Results: The study showed that most of the subject (73%) were using the treatment for the teeth alignment, and only a few were using for the lifestyle purpose only. From all subjects wearing orthodontic appliance, 63% of them were chosen dental quack custom-made orthodontic appliance due to the lower price, and 37% of the rest due to peerâs suggestion who had it before. The combination of the low income with the needs of orthodontic treatment and inadequate information regarding orthodontic appliance such as dental braces affected the subjects preferences towards the dental quack custom-made orthodontic appliance. Overall, the socioeconomic environment is the most influencing factor of preference. Conclusion: A lower price was the most influencing factor of high preferences for the dental quack custom-made orthodontic appliance.